Blockade of MIF–CD74 Signalling on Macrophages and Dendritic Cells Restores the Antitumour Immune Response Against Metastatic Melanoma - Figueiredo, Carlos R.; Azevedo, Ricardo A.; Mousdell, Sasha; Resende-Lara, Pedro T.; Ireland, Lucy; Santos, Almudena; Girola, Natalia; Cunha, Rodrigo L. O. R.; Schmid, Michael C.; Polonelli, Luciano; Travassos, Luiz R.; Mielgo, Ainhoa (Frontiers in Immunology, 2018)
• Mounting an effective immune response against cancer requires the activation of innate and adaptive immune cells. Metastatic melanoma is the most aggressive form of skin cancer. While immunotherapies have shown a remarkable success in melanoma treatment, patients develop resistance by mechanisms that include the establishment of an immune suppressive tumour microenvironment. Thus, understanding how metastatic melanoma cells suppress the immune system is vital to develop effective immunotherapies against this disease. In this study, we find that the innate immune cells, macrophages and dendritic cells are suppressed in metastatic melanoma support instead of inhibiting tumour progression. Treatment of mice bearing metastatic melanoma with the Ig-CDR-based peptide C36L1 is able to restore macrophages and dendritic cells’ immunogenic functions and to inhibit metastatic growth in lungs. Mechanistically, we found that C36L1 interferes with the MIF-CD74 tumour-innate immune cells immunosuppressive signalling pathway and thereby restores an effective anti-tumour immune response. C36L1 directly binds to CD74 on macrophages and dendritic cells, disturbing CD74 structural dynamics and inhibiting MIF signalling through CD74. Our findings suggest that interfering with MIF-CD74 immunosuppressive signalling in macrophages and dendritic cells using peptide-based immunotherapy can restore the anti-tumour immune response in metastatic melanoma. Our study provides the rationale for further development of peptide-based therapies to restore the anti-tumour immune response in melanoma.